Allium elaounii: a new species of A. sect. Pseudoscorodon (Amaryllidaceae, Allioideae, Allieae) from Kroumirian mountains, Tunisia - El Mokni, Ridha (Phytotaxa, 2022)
A new species of Allium, A. elaounii sp. nov. seemingly endemic to Kroumirian mountains (Northwestern of Tunisia) is described and illustrated. The new species is morphologically similar to A. rouyi group and A. valdecallosum, from which it differs mainly by characters of stem, bulb, leaves, inflorescence, and seeds. Distribution in Tunisia, notes of its preferred habitat, phenology, and the IUCN status of conservation are also provided. A diagnostic key to species of the A. sect. Pseudoscorodon occurring in North Africa is also presented.